Analisis Kandungan Protein dan Mutu Organoleptik Biskuit Subtitusi Tepung Kacang Hijau dan Tepung Wortel sebagai Snack untuk Ibu Menyusui - Nafidatul Ummah; Tri Yunita Fitria Damayanti; Dian Ayu Ainun Nafies (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Exclusive breast milk is breast milk that is given to babies from birth for 6 months without adding or replacing it with other foods and drinks. Providing exclusive breastfeeding is not easy thing, many mothers complain about a lack of breast milk. Data BPS (2022) shows that exclusive breastfeeding coverage in East Java is 69.72%, while in Tuban Regency is 48.8%. from the national target of 100%. To increase breast milk production and maintain the quality of breast milk, mothers need high-protein foods or snacks, so biscuits are made to replace mung bean flour and carrot flour as an alternative snack for breastfeeding mothers. The purpose of this study is to determine the effect of mung bean flour and carrot flour substitution on protein value and organoleptic quality of biscuits. This study used True Experimental Design with (RAL), 4 levels of treatment and 6 times replication, with a ratio of wheat flour: mung bean flour: carrot flour in each treatment is P0(100:0:0), P1(70:20:10), P2(60:10:30), P3(50:30:20). The results showed that there was an effect of increasing protein levels in biscuits with the highest value of mung bean flour and carrot flour substitution in the P3 treatment. There was a significant influence on the color, taste, aroma and texture of biscuits shown by the Kruskal Wallis Test (p<0.005) and the Mann-Whitney follow-up test which showed a difference in all treatments. The conclusion of this biscuits substituted with mung bean flour and carrot flour have an effect on protein content and organoleptic quality.